Description of Litomosoides ysoguazu n. sp. (Nematoda, Onchocercidae), a parasite of the tuft-toed rice rat Sooretamys angouya (Fischer) (Rodentia: Cricetidae), and a first record of L. esslingeri Bain, Petit & Berteaux, 1989 in Paraguay - Notarnicola, Juliana (2015)
Paraguay is a small landlocked country whose mammalian fauna is among the least studied in South America, as well as their parasites. As a result of a study of the effects of habitat fragmentation on small mammal biodiversity in eastern Paraguay, we have collected some parasites of cricetid rodents. Herein, we describe a new species of Litomosoides Chandler, 1931 parasitising the body cavity of the tuft-toed rice rat Sooretamys angouya (Fischer) and Litomosoides esslingeri Bain, Petit & Diagne, 1989 parasitising Oligoryzomys nigripes (Olfers), thus expanding its geographical distribution into Paraguay. Litomosoides ysoguazu n. sp. is characterised by the large size of the females (92.2–117.6 mm long) and by having buccal capsule with an anterior widening with rounded edges on the chitinous segment and a rounded widening at the base; male tail with a single pair of adcloacal papillae, three to five pairs of asymmetrical postcloacal papillae, and one or two unpaired papillae in the median ventral line; spicules corresponding to the ‘‘sigmodontis’’ species group; and microfilaria with a sheath stuck to the body and visible in the anterior extremity. We also describe a fourth-stage female larva. Oligoryzomys nigripes is a new host record of L. esslingeri; this enlarges the host record to eight species highlighting the low specificity of this species.